2007
DOI: 10.1177/0898264307300979
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dyadic Social Support on Self-Efficacy and Depression After Radical Prostatectomy

Abstract: Findings confirm pilot study results and are theoretically consistent with the self-efficacy enhancing nature of vicarious experience described by Bandura in self-efficacy theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 40 publications
1
67
0
5
Order By: Relevance
“…91 Males with prostate cancer were the most frequently studied male-only population (n = 15) included in this review. 48,49,52,58,59,61,64-66, 68,69,72,78,80,89 Other disease areas included hypertension (n = 6), 47,71,79,82,83,85,86 COPD (n = 6), 54,55,[73][74][75][76]81,84,87,88 heart failure (n = 4), 62,67,90,91 type 2 diabetes (n = 3), 46,50,51,70 diabetes of unspecified type (n = 1), 56 arthritis (n = 1) 63 and testicular cancer (n = 1). 77 One multimorbidity study recruited obese men with type 2 diabetes and chronic kidney disease.…”
Section: Setting and Samplementioning
confidence: 99%
See 3 more Smart Citations
“…91 Males with prostate cancer were the most frequently studied male-only population (n = 15) included in this review. 48,49,52,58,59,61,64-66, 68,69,72,78,80,89 Other disease areas included hypertension (n = 6), 47,71,79,82,83,85,86 COPD (n = 6), 54,55,[73][74][75][76]81,84,87,88 heart failure (n = 4), 62,67,90,91 type 2 diabetes (n = 3), 46,50,51,70 diabetes of unspecified type (n = 1), 56 arthritis (n = 1) 63 and testicular cancer (n = 1). 77 One multimorbidity study recruited obese men with type 2 diabetes and chronic kidney disease.…”
Section: Setting and Samplementioning
confidence: 99%
“…Three male-only studies 53,68,69 and one mixed-sex study 156 reported self-efficacy outcomes which could be used for meta-analysis. Table 26 reports the effect sizes for each group.…”
Section: Self-efficacy: Positive Scores Indicate Better Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence of improved psychological wellbeing for the recipients of such support [2][3][4], however, findings are inconsistent. It may be that individual characteristics determine who benefits from peer support, and these individual variations may be lost in aggregated data.…”
mentioning
confidence: 86%